If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = 27 + -8x Reorder the terms: 3 + 4x = 27 + -8x Solving 3 + 4x = 27 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 3 + 4x + 8x = 27 + -8x + 8x Combine like terms: 4x + 8x = 12x 3 + 12x = 27 + -8x + 8x Combine like terms: -8x + 8x = 0 3 + 12x = 27 + 0 3 + 12x = 27 Add '-3' to each side of the equation. 3 + -3 + 12x = 27 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = 27 + -3 12x = 27 + -3 Combine like terms: 27 + -3 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 2y+6=-20 | | 12x-30+4x+2= | | 8(x+7)=15x-56 | | 2x-2(2)=2 | | 231-y=118 | | 3x-11+2x+5=180 | | 2(-4)-2y=2 | | 276=219-w | | a=2w-4 | | 432t*t-72*t+3=0 | | y+6=5(x-2) | | -u+271=198 | | 0.18x+0.9(x-3)=0.01(5x-5) | | 432*t*t-72*t+3=0 | | 36-2y=7y | | 2t^2-75t=-3t^3+50 | | 94c+74=4c | | 7x-9=11x+37 | | 6y=25+y | | 17=4x+2 | | 6x+8x-120=104 | | .25x+.10y=9.15 | | 2(Y+1)-3(Y+6)=9 | | 16x-3=189 | | 14+g=24 | | y=5n-3 | | 6x-2=13x-0 | | 4x^2+5=905 | | 6a-1O=7a+3 | | 4+-11=-y | | 4=1.2+a+6 | | 2(n-4)-(6-7n)=8n |